PENGARUH SERVICE RECOVERYTERHADAP LOYALITASPELANGGAN CUCIAN MOBIL DI KOTA JAMBI: THE EFFECT OF SERVICE RECOVERY ON CAR WASH CUSTOMER SATISFACTION IN JAMBI CITY - Sanwani Sanwani (DIGEST MARKETING, 2018)
This study aim is to reveal the influence of service recovery that consistof procedural justice, interactional justice, distributive justice on customer loyalty of car was customer satisfaction. This study used survey research that used questionnaire to collect primary data. Statistical analysis used multiple linear regression analysis. The results showed that the service recovery effect simultaneously on customer loyalty, while partially only interactional justice influence customer loyalty significantly. Hence, it is recommended that firms encourage employees to keep sustain relationship that ensure interaction with customers. Keywords:Customer Loyalty , Distributive Justice, Interactional Justice, Procedural Justice, and Service Recovery